Quality Standards and Competition: Market Access of Peruvian Quality Coffee Beans to Specialized Markets - Calle Roalcaba, Orly Denisse (2010)
Southern Taiwan University (nombre actual de la universidad: Southern Taiwan University of Science and Technology)